Category of topological jet-variables in the theory of nonlinear infinite-dimensional dynamic systems - Prikarpatsky , A. K.; Fil , В. M. (Ukrains’kyi Matematychnyi Zhurnal, 1992)
A new category of topological jet manifolds is proposed for the purpose of investigating exact finite-dimensional approximations of nonlinear dynamical systems on infinite-dimensional functional manifolds. Differential geometry structures on these manifolds and their applications to the theory of integrability in quadratures of nonlinear dynamical Lax-type systems are studied.